PHENOLIC COMPOUNDS FROM INDONESIAN WHITE TURMERIC (CURCUMA ZEDOARIA) RHIZOMES - DYAH UTAMI CAHYANING RAHAYU; DWI AYU SETYANI; HANHAN DIANHAR; PURWANTININGSIH SUGITA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the present study is to isolate phenolic compounds from Curcuma zedoaria rhizomes grown in Bogor, West Java, Indonesia, which will enrich phytochemical information from this plant. Methods: C. zedoaria rhizomes were macerated in methanol then followed by increasing polarity partitions with n-hexane, ethyl acetate (EtOAc), and methanol, respectively. EtOAc fraction was further fractionated using various chromatography techniques to yield two isolated fractions, Z1 and Z2. These two isolated fractions were then characterized to determine their compound structures. Results: According to Fourier transform-infrared, ultraviolet-vis, and liquid chromatography–mass spectrometry (MS)/MS data, Z1 fraction was elucidated as curcuminoid derivative, that is, dimethoxycurcumin (DiMC, 1), while Z2 fraction was yielded as a mixture consisted of flavonoid and coumarin derivatives, that is, 3,5,7-trihydroxy-4’-methoxyflavon (kaempferide, 2) and 7-methoxy coumarin (herniarin, 3). Conclusion: This study reveals useful information regarding phenolic constituents of Indonesian C. zedoaria rhizomes. Further research needs to be carried out to purify other compounds contained and to conduct bioactivity assays.